Studies on fresh milt parameters and cellular changes during cryopreservation of spermatozoa of Deccan mahseer Tor khudree (Sykes, 1839) - Patil, Ravindragouda; Lakra, Wazir Singh; Jahageerdar, Shrinivas; Krishna, Gopal; Pal, Asim Kumar (Indian Journal of Fisheries, 2016)
Studies on the physico-chemical characteristics of seminal plasma, along with ultrastructure and mitochondrial activity of fresh spermatozoa of the endangered Deccan mahseer Tor khudree were undertaken. The ultrastructure and mitochondrial activity of fresh spermatozoa were compared with those of cryopreserved-thawed spermatozoa to understand the nature and extent of cryo-damage. Physico-chemical analyses of fresh milt revealed sperm density of 3.93±0.11 x 107 spermatozoa ml-1, spermatocrit value of 67.08±1.22%, higher K+ concentration of 13.16±0.121 mg l-1, total reducing sugar and total protein concentration of 47.31±0.82 and 19.60±0.66 mg 100 ml-1 respectively. Ultrastructure of the fresh spermatozoa by both scanning (SEM) and transmission electron microscopy (TEM) revealed the spherical head without any acrosomal complex, small mid piece with mitochondria and a long tail. Cross section of tail by TEM revealed typical 9+2 doublet arrangement of the axoneme. Head measured 1.86±0.006 μ in dia with a mid-piece length of 0.53±0.012 μ and tail length of 33.53±0.220 μ. Ultrastructural damages to the spermatozoa following cryopreservation included, loosening of chromatin and disruption of the cytoplasmic membrane as compared to that of fresh spermatozoa. Nitroblue tetrazolium (NBT) assay revealed low levels of activity of the enzymes of the mitochondrial complex in cryopreserved-thawed spermatozoa when compared to fresh spermatozoa indicating damage to the functional integrity of the enzymes of the mitochondrial enzyme complex.